Ab Initio and Density Functional Predictions of Solvation Free Energies of Cyclic Polyethers (CH2CH2O)n (n=2,6) in Aqueous and Tetrachloromethane Solutions - Ariche, B.; Rahmouni, A.; Brahim, H.; Guendouzi, A.; Alali, K. (Journal of Applied Solution Chemistry and Modeling, 2013)
Solvation free energies ΔGsoltot of cyclic polyethers (CH2CH2O)n (n=2,6) in aqueous and tetrachloromethane solutions have been calculated at HF, MP2 and B3LYP/6-311G (d,p) levels of theory using CPCM, IEFPCM and SMD implicit solvation models. It has been found that ΔGsoltot are negative for both solvents, they increase linearly with system sizes and they are more important in water solution. The electrostatic contributions to the solvation free energies ΔGsolele are also more important in water because of their polar nature. In water, CPCM and IEFPCM models give a close values, which are slightly different from SMD values. In tetrachloromethane solvent CPCM model seems overestimate ΔGsolele. For both solvents the non-electrostatic contributions to the solvation free energies ΔGsoln-ele provided by SMD are remarkably different to those given by CPCM and IEFPCM models. <!-- [if gte mso 9]> Normal 0 21 false false false FR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->